Pendampingan Aktivitas Be a Digital Exporter Program Studi Independen Bersertifikat Pada Mitra Sekolah Ekspor Nasional - Hardi Alunaza; Mentari Mentari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Students face various challenges related to international trade skills. These include a lack of practical understanding, cultural differences and communication skills, knowledge of export regulations and policies, adaptation to new technologies, negotiation skills, and foreign language proficiency. The Studi Independen is one of the Merdeka Belajar programs by the Ministry of Education and Culture. This project encourages students to collaborate with industries, ensuring that the curriculum learned by student is relevant to workforce needs. The community service activity in the form of the